TELAAH KRITIS: BUKU MATEMATIKA UNTUK SMA KELAS X (EDISI REVISI 2023) KURIKULUM MERDEKA MATERI ANALISIS DATA - Nurfadilah; Kasmawati; Muhammad Ammar Naufal (Afore : Jurnal Pendidikan Matematika, 2026)
This critical review aims to evaluate the Grade X Senior High School Mathematics textbook (2023 Revised Edition) of the Kurikulum Merdeka, specifically on the Data Analysis topic. This study employs a qualitative descriptive method using document analysis to assess various aspects, including the consistency of the conceptual map, the relevance of the material to learning objectives, the essence of the content, and the strengths and weaknesses of the book's substance. The findings indicate that the textbook generally covers the fundamental concepts of descriptive statistics and is highly relevant in supporting the development of students' data literacy and interpretation skills through real-life contexts. However, several significant weaknesses were identified, such as a conceptual map structure that is not fully hierarchical and lacks consistent connecting words, the use of unconventional terminology, and learning objectives that do not fully meet the ABCD (Audience, Behavior, Condition, Degree) operational criteria. Furthermore, some exercises still tend to emphasize routine calculation procedures rather than deep reasoning, and there is a high dependency on the teacher's ability to facilitate discussions. Based on these findings, it is recommended to revise the systematic structure of the material map, refine the learning objectives to be more measurable, and strengthen content that encourages Higher Order Thinking Skills (HOTS) through technology integration and reflective activities.